Neuere Imperiumsforschung in der Osteuropäischen Geschichte:: die Habsburgermonarchie, das Russländische Reich und die Sowjetunion - Jobst, Kerstin S.; Obertreis, Julia; Vulpius, Ricarda (Comparativ, 2008)
Research on Empires in the historiography on Eastern Europe Since the 1990s, research in East European History has been deeply influenced by the concept of empire and reinvigorated by the growing interest in the complexities of the multinational and multi-confessional character of the area. It is the goal of this contribution not only to showcase the recent scholarship on the Habsburg Monarchy, the Russian Autocracy and the Soviet Union as empires, but also to address the most interesting questions that are currently pushing the field in new directions. All three cases reveal that neither the difference between maritime and continental empires, often overemphasized in earlier scholarship, nor the distinction between seemingly “modern” (Western) and “backward” (Eastern) empires can be sustained. The peculiarities of all three empires highlight rather the central question of to what extent these cases were empires at all, and of the development of the relationship between the national and imperial traits of the various states.